1995
DOI: 10.1016/0735-1097(95)00084-h
|View full text |Cite
|
Sign up to set email alerts
|

Dobutamine stress echocardiography in orthotopic heart transplant recipients

Abstract: Dobutamine stress echocardiography is a useful technique for the diagnosis of coronary artery disease after heart transplantation. These preliminary results indicate that dobutamine stress echocardiography may have a predictive value for further ischemic events in heart transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 26 publications
3
32
0
1
Order By: Relevance
“…5 Dobutamine stress echocardiography is useful 6 but, even in selected populations, 5% of patients referred for this test have inadequate acoustic window and 10% have nondiagnostic (sub-maximal negative) results. 6,7 Perfusion single photon emission computed tomography (SPECT) has a low sensitivity in patients with denervated heart and submaximal exercise test. 8 The addition of electrocardiographic gating increases the diagnostic accuracy of perfusion SPECT and provides reproducible information on left ventricular (LV) function.…”
Section: Introductionmentioning
confidence: 98%
“…5 Dobutamine stress echocardiography is useful 6 but, even in selected populations, 5% of patients referred for this test have inadequate acoustic window and 10% have nondiagnostic (sub-maximal negative) results. 6,7 Perfusion single photon emission computed tomography (SPECT) has a low sensitivity in patients with denervated heart and submaximal exercise test. 8 The addition of electrocardiographic gating increases the diagnostic accuracy of perfusion SPECT and provides reproducible information on left ventricular (LV) function.…”
Section: Introductionmentioning
confidence: 98%
“…61,62 When intimal thickening by intravascular ultrasound is taken as the "gold standard," dobutamine stress echocardiography shows specificities of up to 88%. 63,64 Moreover, a predictive value of dobutamine stress echocardiography for development of future CAV and outcome has been described.…”
Section: Dobutamine Stress Echocardiographymentioning
confidence: 99%
“…Unlike with ESE, a number of studies have compared DSE vs ANG in children. 1,2,[5][6][7][8][9] One study of 70 pediatric heart transplant patients found the sensitivity and specificity values of DSE were 72% and 80%. 6 In another study of 102 pediatric heart transplant recipients, DSE had a sensitivity of 35% and specificity of 94%.…”
Section: Discussionmentioning
confidence: 98%